The Impact Of Short Run Distances To The Final Results Of The Decathlon At The 2019 Athletic World Championships - L Ramadani; G Heta; L Bekolli; N Rashiti; Q Ramabaja; A Millaku (Kazimierz Wielki University, 2019)
Athletic operates on the basis of a particular system of knowledge that has in its contentthe theoretical and methodological foundations of sport training (Rashiti N, Nika F, Bekolli L, Heta G.) 2017. Athletic is one of the types of sports, with complex and applicable character, consisting of large groups, which include different athletic types, with similar characteristics among them; our treatment is athletic decathlon.(Dibra F.)2006. The decathlon is a complexcombined event in athletic consisting of ten track and field events.Olympic men's decathlons are divided into a two-day competition. The evaluation is done by points.Men's decathlonconsists of:100m,Long jump,Shot put,High jump, 400m (Day 1); 110m hurdles,Discus throw,Pole vault,Javelin throw,1500m(Day 2). The main purpose of this paper was to verify that from the disciplines of the Decathlon:Long jump,Shot put,High jump, Discus throw,Pole vault,Javelin throw and1500m,as predictor (independent) variables will have an impact on the performance of specific motor tasks, respectively the execution of disciplines pertaining to short-distance running:100m, 110m  hurdles and 400mas well as to determine the impact of these short-distance running to the final result of the decathlon knowing that these disciplines in athletics are largely genetically determined.(Misja B.) 2012 The sample for the purposes of this paper will include 10 first contestants of decathlons World Championship: September 27 and October 6, 2019 in Doha, Qatar.In this research, after obtaining a statistically significant multiple correlation (R = 0.936) it is necessary to search for the coefficient in the (Beta) column as well as the (t-test) value indicating the influence of each predictor variable (independent) in the dependent or criterion variable 400m.We can emphasize that the test (F-test) is always more valuable if the multiplex correlation is greater, in this case it is significant (Sig = 0.000), because the value of the F-test is 15,347.A statistically significant multiple correlation was obtained (R = 0.958); it is necessary to search for the coefficient in the (Beta) column as well as the (t-test) value indicating the influence of each predictor (independent) variable in the dependent variable or criterion 110 m. In this research, after obtaining a statistically significant multiple correlation (R = 0.958), it is necessary to search for the coefficient in the (Beta) column as well as the (t-test) value indicating the influence of each predictor variable (independent) in the dependent or criterion variable) 100 m.